STRUCTURAL STUDY OF BIS(2,6-BIS(PYRAZOL-3-YL)PYRIDINE)NICKEL(II) BY CALORIMETRY AND EXAFS SPECTROMETRY - Kristian H Sugiyarto (Indonesian Journal of Chemistry, 2003)
The main aim of this work is to reveal the complex formation of 2,6-bis(pyrazol-3-yl)pyridine, bpp, with nickel(II) perchlorate in DMF by calorimetric stepwise complex formation and then followed by EXAFS spectrometry. It was found that the complex formation follows two stepwise pathways namely the formation of mono pyrazolyl-pyridine, [Ni(DMF)3 bpp]2+, and bis pyrazolyl-pyridine, [Ni(bpp)2]2+;  the formation constants being  log β1 = 6.57, and log β2 = 5.02, and the total value of log β  = 11.58. The final formation of six-coordinated compound was confirmed by EXAFS analysis with the mean Ni-Nbpp bond length of 2.0646(0.0014) Å.